Pengaruh Brand Image, Kualitas Produk, Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan - Rohiman, Dede; Sarah, Siti (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to analyze how customer happiness is impacted by brand image, product quality, and service quality. combining descriptive and verification techniques with a quantitative approach. Questionnaires, interviews, and literature reviews were used to gather data, and the Slovin formula was used to choose a sample of 20 respondents. With a t value of -0.567 and a significance value of 0.578, the study using SPSS 25 revealed that brand image had no discernible impact on customer satisfaction. Service quality has a considerable impact with a t value of 3.491 and a significance value of 0.003, whereas product quality has a t value of 1.809 and a significance value of 0.009. With a simultaneous F value of 20.380 and a significance level of 0.000, the three factors strongly influence customer satisfaction.